Analysis of Public Services to Improve Service Excellence in Bugoharjo Village - Rochman, Mohammad Zubairi; Wulandari, Siti Sri (Journal of Office Administration : Education and Practice, 2023)
This research analyzes how public services improve great service in Bugoharjo Village, Pucuk District, Lamongan Regency. This study employs a descriptive research method with a qualitative approach, in which the data and information acquired are described in line with the facts in the field and then given in the form of a narrative sentence before concluding. This study will be conducted at the Bugoharjo Village office in Pucuk District, Lamongan Regency. Observation, interviews, and documentation were utilized to obtain data. Source triangulation is the method employed by researchers. Researchers employ the data analysis steps of reduction, display, and conclusion/verification. This research was conducted using interviews and direct observation, yielding data on five different topics: 1) Tangible aspects (real evidence); 2) Reliability aspect (reliability); 3) Responsiveness aspect (responsiveness); 4) Assurance aspect (guarantee); 5) Empathy aspect (empathy). On the surface, the facilities and infrastructure of the Bugoharjo Village Office are relatively complete, but some aspects, such as the service waiting area, might be improved. In terms of dependability or dependability, Bugoharjo has adequately prioritized the quality of its services. In terms of reactivity, the Bugoharjo village office staff are not sufficiently responsive in providing services. Furthermore, in terms of assurance or assurance, it is okay; it is simply that the level of staff discipline needs to be improved again. In terms of empathy, the Bugoharjo village office personnel have used it effectively in providing services, leaving the community quite satisfied.